Counting only the hits? The risk of underestimating the costs of stringent climate policy - Massimo Tavoni; Richard S.J. Tol (The Economic and Social Research Institute (ESRI), 2009)
This paper warns against the risk of underestimating the costs -and the uncertainty about the costs- of achieving stringent stabilization targets. We argue that a straightforward review of integrated assessment models results produces biased estimates for the more ambitious climate objectives such as those compatible with the 2 °C of the European Union and the G8. The magnitude and range of estimates are significantly reduced because only the most optimistic results are reported for such targets. We suggest a procedure that addresses this partiality. The results show highly variable costs for the most difficult scenarios.
Keywords: 330; Umweltpolitik; Klimaschutz; Kosten; Wohlfahrtseffekt; EU-Staaten; G-8-Staaten